(untitled) (TAMADDUN NURI JURNALI, 2025)
This article explores the historical study of euphemisms in the Uzbek language and identifies key reasons for their emergence, such as cultural, religious, and social influences. It also includes a linguistic analysis of euphemisms commonly used in modern Uzbek speech and their communicative functions. Special attention is paid to taboo vocabulary and its replacement through euphemistic expressions.